2019
DOI: 10.3389/fphar.2018.01529
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-Driven Virtual Panel Is an Effective Method to Analyze WES Data of Neurological Disease

Abstract: Objective: Whole Exome Sequencing (WES) is an effective diagnostic method for complicated and multi-system involved rare diseases. However, annotation and analysis of the WES result, especially for single case analysis still remain a challenge. Here, we introduce a method called phenotype-driven designing “virtual panel” to simplify the procedure and assess the diagnostic rate of this method.Methods: WES was performed in samples of 30 patients, core phenotypes of probands were then extracted and inputted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The number of VUS might be much more increased in the regular laboratory setting with limited clinical information. Overall, our results support the use of an exome-based panel for muscular disorders, although several considerations must be taken into account when introducing exome-based panel in the laboratory [38][39][40] (table e-6, links.lww.com/NXG/A239).…”
Section: Discussionsupporting
confidence: 64%
“…The number of VUS might be much more increased in the regular laboratory setting with limited clinical information. Overall, our results support the use of an exome-based panel for muscular disorders, although several considerations must be taken into account when introducing exome-based panel in the laboratory [38][39][40] (table e-6, links.lww.com/NXG/A239).…”
Section: Discussionsupporting
confidence: 64%
“…WES employs NGS platforms, such as Illumina, to sequence the protein-coding regions of the genome. Although initial sequencing and analysis of the human genome revealed that less than 2% of the genome comprises exons, approximately 85% of the DNA variations responsible for highly penetrant genetic diseases lie in this small fraction of the genome [ 6 , 7 ]. Currently, WES is the most commonly used mainstream sequencing method in clinical applications due to its low associated cost and turnaround time, compared with WGS.…”
Section: Ngs Toolsmentioning
confidence: 99%
“…Thus, WES facilitated landmark changes in the management and treatment of diseases based on the identification of causal genetic factors. With further development of sequencing technology, the diagnostic rate across diverse clinical laboratories increased to 65.52% [ 7 ]. However, the overall diagnosis rate remains low, primarily due to challenges associated with the detection of pathogenic mutations, which may be classified as a VUS or appear within the noncoding region, thus escaping capture by WES.…”
Section: Ngs Toolsmentioning
confidence: 99%
“…Whole-exome sequencing (WES) and Sanger sequencing were performed by Running Gene Inc. (Beijing, China) using their standard process, which is available in the previous report [8]. The variant c.1283insC (GRCh37/ hg19, NM_000944) of PPP3CA was identified in the proband.…”
Section: Next-generation Sequencingmentioning
confidence: 99%